Pengaruh Persepsi Bauran Pemasaran Terhadap Loyalitas Pasien Poliklinik (Non-JKN) Di Rumah Sakit Adi Husada Kapasari - Kamalin, Fajriatul; Mamesah, Marline Merke; Wijaya, Hermanto; Setiawan, Liman (Journal of Health Management Research, 2024)
Background: Based on observations at Adi Husada Kapasari Hospital, it was recorded that there was a decrease in the number of patient visits during the first quarter of 2024. Aims: The objective of this research was to determine the influence of perceptions about the marketing mix on the loyalty of outpatients (Non-JKN) at Adi Husada Kapasari Hospital, Surabaya. Methods: This research uses quantitative methods with a cross-sectional research design. A sample of 30 respondents. Results: The research results indicate that perceptions of the product (P-value 0.019), promotion (P-value 0.028), process (P-value 0.000), and physical evidence (P-value 0.015) have an influence on patient loyalty. However, perceptions of place (P-value 0.059), price (P-value 0.147), and people (P-value 0.147) do not show a significant influence on patient loyalty. Conclusion: Based on perceptions of the 7P marketing mix, there are differences in the level of significance of the influence of various elements on patient loyalty. Product, process, promotion, and physical evidence are found to have a very significant impact on patient loyalty, while place, price, and people do not always show a significant direct influence on patient loyalty behavior.